2018
DOI: 10.17509/ijal.v7i3.9797
|View full text |Cite
|
Sign up to set email alerts
|

Theme and Thematic Progression in Students’ Recount Texts

Abstract: This study aims to investigate the Theme and Thematic progression patterns in students' recount text in a state vocational school in Bandung. This study employs a descriptive-qualitative research design. The data were obtained from a collection of students' texts. This study uses the theory of Theme system developed by Halliday (1994) and the theory of Thematic progression proposed by Eggins (2004) as the framework to analyze the data. The findings showed that the Theme and Thematic progression supports the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 5 publications
5
34
1
2
Order By: Relevance
“…The difference is caused by the nature of news item text that frequently highlights the time and the place of the reported events. In addition, the findings of this research are contradictory with the findings of the research on narrative texts done by Nurlela et al [22]. They found that Indonesian narrative texts are characterized by the frequent use of marked themes and multiple themes.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The difference is caused by the nature of news item text that frequently highlights the time and the place of the reported events. In addition, the findings of this research are contradictory with the findings of the research on narrative texts done by Nurlela et al [22]. They found that Indonesian narrative texts are characterized by the frequent use of marked themes and multiple themes.…”
Section: Resultscontrasting
confidence: 99%
“…As historical text is a part of recount text, this finding supports Yunita's study, finding the frequent use of simple theme in recount texts [22]. However, this finding is in contrast with Sofyan and Tarigan's study whose findings show that marked theme is the theme most frequently used in Indonesian news item texts [12].…”
Section: Resultssupporting
confidence: 77%
“…The researcher's basis I n P r e s s is to investigate thematization in periodicity (SFL) in text Kuroino. Besides, considering objectives of this research to examine patterns in theme development and information distribution, which is coherence in the text is by combining the theory of thematic progression stated by Danes in (Kizil & Kushch, 2019) and Eggins in (Gunawan & Aziza, 2017;Yunita, 2018), namely thematic progression with a linear theme, thematic progression with a continuous (constant) theme, and thematic progression with derived themes.…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis is conducted to answer problems in this research; (1) to analyze verbal text (35 clauses) using a theory of three metafunctions of language, namely ideational meaning, interpersonal meaning, and textual meaning by Halliday & Matthiessen (2014) and thematic progression by Danes in (Kizil & Kushch, 2019) and Eggins in (Gunawan & Aziza, 2017;Yunita, 2018); and (2) to analyze visual text using three metafunctions of the image by Kress & van Leeuwen (2020), including representational meaning, interactive meaning, and compositional meaning. After conducting the analysis, in the discussion section, the researcher sees the relevance of meaning in verbal and visual texts based on the relationship stated by Liu (2019), whether or not it creates a relation with synergy and meaning.…”
Section: Methodsmentioning
confidence: 99%
“…The researcher draws a conclusion based on previous studies that using thematic progression patterns to solve students' writing problems is a good choice. Meanwhile, (Yunita, 2018) focused on the Theme and Thematic development patterns of recount texts written by vocational students, as well as the patterns of dominance constructed by the students in their writing and the representation of Theme elements with students' writing abilities.…”
Section: Introductionmentioning
confidence: 99%